Approaching diversity in Speech Studies: New methodologies under empirical perspectives - Bossaglia, Giulia; Mello, Heliana; Raso, Tommaso (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2016)
Spoken studies have experienced a new step of development during the last ten-fifteen years, due to the advancement of prosodic studies as well as the publication of third generation spoken corpora that allow for text-to-speech alignment, with a growing attention to acoustic quality. In this special issue, seventeen papers dedicated to various linguistic levels and assuming different theoretical and methodological perspectives have been gathered. All papers, however, have as their common basis an empirical approach, devoted to the compilation and study of genuine natural data, added to a strong attention to what these data allow to be said about both speech segmentation and linguistic analysis, taking into account all the information conveyed by the acoustic signal.